Effects of testosterone and vitamin D on fall risk in pre-frail hypogonadal men: a factorial design RCT - Heike A. Bischoff-Ferrari; Melanie Kistler-Fischbacher; Stephanie Gaengler; Thomas Münzer; Bess Dawson-Hughes; Wei Lang; Robert Theiler; Andreas Egli; E. John Orav; Gregor Freystaetter (The Journal of Nutrition, Health and Aging, 2024)
Objective: To test whether transdermal testosterone at a dose of 75 mg per day and/or monthly 24’000 IU Vitamin D reduces the fall risk in pre-frail hypogonadal men aged 65 and older. Design: 2 × 2 factorial design randomized controlled trial, follow up of 12 months. Methods: Hypogonadism was defined as total testosterone <11.3 nmol/L and pre-frailty as ≥1 Fried- frailty criteria and/or being at risk for falling at the time of screening. The primary outcomes were number of fallers and the rate of falls, assessed prospectively. Secondary outcomes were appendicular lean mass (ALM), sit-to-stand, gait speed, and the short physical performance test battery. Analyses were adjusted for age, BMI, fall history and the respective baseline measurement. Results: We aimed to recruit 168 men and stopped at 91 due to unexpected low recruitment rate (1266 men were pre-screened). Mean age was 72.2 years, serum total testosterone was 10.8 ± 3.0 nmol/l, and 20.9% had 25(OH)D levels below 20 ng/mL. Over 12 months, 37 participants had 72 falls. Neither the odds of falling nor the rate of falls were reduced by testosterone or by vitamin D. Testosterone improved ALM compared to no testosterone (0.21 kg/m2 [0.06, 0.37]), and improved gait speed (0.11 m/s, [0.03, 0.20]) compared to placebo. Conclusion: Transdermal testosterone did not reduce fall risk but improved ALM and gait speed in pre-frail older men. Monthly vitamin D supplementation had no benefit.